2018
DOI: 10.1108/ijoem-08-2017-0313
|View full text |Cite
|
Sign up to set email alerts
|

The transition probabilities for inflation episodes in Ghana

Abstract: Purpose Following the reforms in monetary policy and shift in fiscal policies, it is logical to presume that these reforms may cause a significant structural change in the dynamic processes of inflation and hence affect the nature of inflation persistence. The purpose of this paper is to examine the persistence nature of the different inflation episodes while controlling for the effects of demand- and supply-side factors, which are modeled as regime-dependent. Design/methodology/approach This paper used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…They confirmed that the Bayesian VAR models perform better than the DSGE models to forecast inflation in Sweden. In the case of low and high inflation regimes, Adom et al (2018) monitor supply and demand factors to keep pace with continuing inflation in Ghana. Their Markow-switching dynamic regression model suggests that both factors are meaningful for inflationary inertia and that the high inflation regime is more persistent than the low inflation regime.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They confirmed that the Bayesian VAR models perform better than the DSGE models to forecast inflation in Sweden. In the case of low and high inflation regimes, Adom et al (2018) monitor supply and demand factors to keep pace with continuing inflation in Ghana. Their Markow-switching dynamic regression model suggests that both factors are meaningful for inflationary inertia and that the high inflation regime is more persistent than the low inflation regime.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, inflation can lead to the failure of important policies or projects because it disrupts budget allocation, ultimately hindering the economic progress. Considering the adverse consequences of inflation is likely to have on economies as well as the livelihood and welfare of citizens, the dynamics of inflation, money supply and budget deficit have continuously received attention from both theoretically and empirical perspectives (Adom et al, 2018). Different scholars employ different methods to describe the phenomenon of inflation.…”
Section: Introductionmentioning
confidence: 99%